1994
DOI: 10.1071/bt9940383
|View full text |Cite
|
Sign up to set email alerts
|

A Floristic Comparison of Vascular Species in Tasmanian Oldgrowth Mixed Forest With Regeneration Resulting From Logging and Wildfire

Abstract: About 20% of Tasmania's wet eucalypt forest is mixed forest, i.e. having a rainforest understorey and a eucalypt overstorey. While one-third of the mixed forest is formally reserved, much of the remainder is subject to logging on an 80-100 year rotation which is insufficient for the redevelopment of mature mixed forest. The routine silvicultural regeneration treatment for wet eucalypt forests is to clearfell, burn and sow with eucalypt seed. A comparison of the Vascular floristics of 20-30-year-old silvicultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
84
2
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(92 citation statements)
references
References 8 publications
5
84
2
1
Order By: Relevance
“…Several authors have reported reduced occurrence or absence of epiphytic ferns after harvesting (e.g. Harris, 1989;Ough and Ross, 1992;Hickey, 1994). Tree-ferns greater than 1.5 m tall support epiphytic species much more commonly than smaller tree-ferns (personal observation).…”
Section: Implications Of Tree-fern Decline For Other Speciesmentioning
confidence: 95%
“…Several authors have reported reduced occurrence or absence of epiphytic ferns after harvesting (e.g. Harris, 1989;Ough and Ross, 1992;Hickey, 1994). Tree-ferns greater than 1.5 m tall support epiphytic species much more commonly than smaller tree-ferns (personal observation).…”
Section: Implications Of Tree-fern Decline For Other Speciesmentioning
confidence: 95%
“…Eles são considerados importantes indicadores ecológicos e o seu monitoramento permite avaliar os efeitos da perturbação florestal (TURNER et al, 1994;HICKEY, 1994;HIETZ, 1999) bem como o seu estágio sucessional (KERSTEN & KUNIYOSHI, 2009). …”
Section: Introductionunclassified
“…Under scenario 3 the populations diverged 224 generations ago (T1, median value), the effective population size of Tasmania was nearly eight times larger than the central highlands Victoria (9500 versus 1230, respectively, median values; see Supplementary Tables S3 and S4 and Supplementary Figure S7 for detailed results of approximate Bayesian computation analysis). This implied a divergence time of 22 400 years ago assuming the generation time of 100 years estimated by Hickey (1994). Mean relative bias values were generally low ( Supplementary Table S3) indicating that estimates are relatively accurate.…”
Section: Timing Of Isolation Across Bass Straitmentioning
confidence: 99%